Pandemic influenza outbreak detection and response in Farta district, South Gondar zone, Amhara region, Ethiopia, 2016 - Ayal Ejigu, Alie; Assefa, Mekonnen; Tilahun, Marelign; Tilahun Zewdu, Feleke (International Research in Medical and Health Sciences, 2018)
Background: Influenza is the most contagious respiratory diseases having significant public health problem. It is associated with higher morbidity and mortality during outbreak, especially among elderly and children. The aim of the study was to investigate the outbreak, magnitude, identify risk factors, and implement public health control measures. Methods: We conduct case–control study in Farta district from February 12 to 29th February 2016. We selected 172 cases and 172 controls (1:1). We used face-to-face interview using structured questionnaire. Data were entered and analyzed using Epi-info7 and SPSS. We used logistic regression analysis to explore predictors of influenza. Results: From February 12 to February 30, 2016, we identified 172 cases (attack rate, 10.38/1000) and two deaths. From total cases, 11 (6.4%) confirmed and 23 (13.4%) admitted cases were reported. Female cases were 51.74 %. Majority affected age groups were <5 and 15–44 years with attack rates of 16.81 and 10.36 per 1000 risk populations, respectively. In multivariable analysis (adjusted odds ratio [95% confidence intervals]), being female (2.76 [1.11, 8.32]), family size ≥5 (3.26 [1.12, 14.59]), presence of traveling history to epidemic area before 7 days before onset of the illness (10.57 [1.34, 42.79]), and having knowledge to influenza illness (0.13 [0.02, 0.91]) were associated factors to the respective variables. Conclusion: Most of the cases were female and 15–44 year’s age. Being female, living in large family size and presence of traveling history to epidemic area before 7 days before onset of the illness were statistically significant risk factors; whereas, having knowledge to influenza illness was protective factors. Health education should be continued to successfully contain the outbreak.